Partial lung lobectomy with the Caiman® Seal & Cut device in a dog with spontaneous pneumothorax: case report - Anne Zobel; Thomas Rohwedder; Peter Bottcher (Open Veterinary Journal, 2022)
Background: Spontaneous pneumothorax in dogs is characterized by an accumulation of air in the interpleural space without an underlying trauma and consecutive acute onset of respiratory distress. Underlying causes for spontaneous pneumothorax vary with ruptured bullae being one of the main causes. Treatment after initial stabilization often requires partial or complete surgical resection of effected lung lobes. Partial lung lobectomy can be performed with stapling devices or sealing devices e.g. by different surgical approaches including video-assisted thoracoscopic surgery. However, intra-thoracic surgery in small sized dogs using either of the techniques is challenging. Case Description: A 12 year old Shih Tzu was presented with spontaneous pneumothorax. Further diagnostics with computed tomography and intercostal thoracoscopy revealed a bulla in the right middle lung lobe. Partial lung lobectomy (2,5cm x 2,5 cm x 2cm) of the respective lung lobe was performed by an intercostal approach using the Caiman® 5 Seal & Cut sealing device. The Caiman® 5 Seal & Cut device allowed quick and safe partial lung lobectomy in the treatment of spontaneous pneumothorax without intra- or post-operative complications. The dog was discharged 2 days after surgery in good clinical condition. This report demonstrates the in-vivo efficacy and safety of the Caiman® 5 Seal & Cut sealing device for partial lung lobectomy in a small breed dog. Conclusion: Using the Caiman® 5 Seal & Cut device lung tissue could be resected without intra- or post-operative complications in a small breed dog. The present case may emphasize the use of the device in fully video-assisted thoracoscopic surgery also in small sized patients. [Open Vet J 2022; 12(6.000): 910-918]